Kinerja Simpang Tak Bersinyal Pada Simpang Parung Bingung (Sawangan Depok) - Rikki Sofyan Rizal; Eko Wiyono; Imtinan Safinatun Naja; Mira Aulia Fita Sari (Universitas Widyatama, 2022)
Congestion often occurs at several points in the city of Depok, West Java. From the monitoring of google maps and direct site inspection, traffic conditions at the Parung Bingung Sawangan Intersection were observed to be quite severe. Congestion occurs due to the high volume of vehicles and the service level of poor Intersection performance. This final project research aims to analyse the dominant factors of the problems that occur at Intersection Parung Bingung in order to solve the problems that occur. The method used is manual analysis with the 2014 PKJI guidelines using primary data obtained from the results of a site survey and secondary data obtained from the Central Statistics Agency of Depok City, Depok City Transportation Service and various journals. The results of the research on the performance of the Unsignalized Intersection of Parung Bingung Intersection in category F (very bad), Degree of Saturation (DJ) above 0.85, High Delay (T) 124.09 sec/skr, Vehicle Volume 5811.06 skr/hour with Road Capacity (C) of 2810.98 cur/hour, and the queue probability (PA) is 156% the upper limit and 75% the lower limit. Therefore, the last alternative that is most appropriate is chosen by using a combined alternative between eliminating or reducing side barriers by installing stop signs, widening roads and changing traffic directions during rush hour.